AN ANALYSIS OF THE STUDENTS’ CONVERSATION PERFORMANCE OF EIGHT GRADE STUDENTS OF SMPS KATOLIK AURORA KEFAMENANU - Nahak, Kristina D. H.; Kamlasi, Imanuel; Lasi, Febronia (Jurnal Edulanguage: Jurnal Pendidikan Bahasa, 2021)
This study concerned speaking, especially in the English conversation. It aims at knowing the students’ speaking English ability in conversation and the students’ difficulties in English conversation. The population of this study is the second-year students of SMPS Katolik Aurora, Kefamenanu and the sample of this study is 20 students. The research design uses a descriptive quantitative method to provide a clear description of students’ speaking ability in conversation. The instrument of this research is a conversation test for students to perform. The result shows that the students’ speaking English ability in conversation is good because the average score is 74.89. The students’ difficulties in English conversation in terms of; vocabulary is 85.25 %, pronunciation is 74 %, fluency is 73.5%, and grammar is 72 %.